Teaching Strategies 1 : For the Teaching of the Communication Arts - Listening, Speaking, Reading, and Writing - Alcantara, Rebecca D.; Cabanilla, Josefina Q. ; Espina, Felicidad P. ; Villamin, Araceli M. (Quezon City, 2003)
This book provides educators with effective strategies for teaching communication arts, focusing on the four key language skills: listening, speaking, reading, and writing.
Keywords: Teaching principles; Teaching strategies